1971
DOI: 10.1901/jaba.1971.4-77
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF ACCESS TO A PLAYROOM ON THE RATE AND QUALITY OF PRINTING AND WRITING OF FIRST AND SECOND‐GRADE STUDENTS1

Abstract: The major dependent variable was the rate at which first and second-grade students printed or wrote daily copying assignments. Data were also taken on the percentage of letters scored as errors according to a set of scoring criteria. Initially, these data were collected during a baseline condition in which each child returned to his seat as soon as his completed work had been scored, to wait for the rest of the class to finish their assignments. When the children were allowed to go to a playroom after their pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 9 publications
3
32
0
Order By: Relevance
“…This supports and extends the findings obtained by Hopkins et al (1971). Following a graduated sequence of reductions, children maintained their performance gains when temporal limits were returned to the former classroom routine.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This supports and extends the findings obtained by Hopkins et al (1971). Following a graduated sequence of reductions, children maintained their performance gains when temporal limits were returned to the former classroom routine.…”
Section: Discussionsupporting
confidence: 87%
“…But some data suggest that the opposite procedure of reducing temporal limits may increase rate of academic performance. Hopkins, Schutte, and Garton (1971) demonstrated that when first and second graders were allowed to go immediately to a playroom after their papers had been scored, rate of printing increased. Later, when the time limits to complete the work and then play were gradually reduced, there was a correlated, progressive increase in rate of printing.…”
mentioning
confidence: 99%
“…Similar to other studies (Evans and Oswalt, 1968;Hopkins, Schutte, and Garton, 1971;Lovitt, Guppy, and Blattner, 1969), the present results indicate the use of free time to be a powerful consequence for the control of a variety of academic behaviors. Leaving school early at the end of the school day and leaving the classroom early for lunch were effective consequences for increasing the number of students completing the homework assignment and for increasing the accuracy with which students performed the homework assignment.…”
Section: Resultssupporting
confidence: 90%
“…Early studies found that teacher attention could be altered to provide an immediate and natural system for changing on-task rates (Chadwick and Day, 1971;Hall et al, 1968;Hasazi and Hasazi, 1972;Ward and Baker, 1968). However, attention was not always effective as a reinforcer, 5Brigham, Finfrock, Breunig, and Bushell, 1972;Chadwick and Day, 1971;Hall and Broden, 1967;Harris and Sherman, 1973;Hasazi and Hasazi, 1972;Hopkins, Schutte, and Garton, 1971;Jacobson, Bushell, and Risley, 1969;Knapczyk and Livingston, 1973;Lahey, McNees, and Brown, 1973;Martin, England, Kaprowy, Kilgour, and Pilek, 1968;Miller and Schneider, 1970;Salzberg, Wheeler, Devar, and Hopkins, 1971; Wolk, Giles, and and token systems with more potent backups became popular alternatives (O'Leary and Becker, 1967, p. 637;Quay, Werry, McQueen, and Sprague, 1966). Studies that dealt with token systems typically dropped the analysis of adult attention and emphasized instead the effect of nonsocial consequences on appropriate classroom behavior.…”
mentioning
confidence: 99%
“…Promptly, however, some researchers began examining the effect of another class of more-natural reinforcers-play activities and materials, and free time. These "natural" reinforcers were found in the home (Nordquist and Wahler, 1973;Phillips, 1968), in psychiatric institutions (Ayllon and Azrin, 1968;Mitchell and Stoffelmayr, 1973), and in educational settings for children and adolescents.6 It has been argued that natural reinforcers should be used whenever 6Betancourt and Zeiler, 1971;Brigham et al, 1972;Harris and Sherman, 1973;Hopkins et al, 1971;Jacobson et al, 1969;Knapczyk and Livingston, 1973;Miller and Schneider, 1970;Osborne, 1969;Reynolds and Risley, 1968;Salzberg et al, 1971;Wolf et al, 1968. possible because they should facilitate generalization of behavior change (Axelrod, 1971;Lovaas, Koegel, Simmons, and Long, 1973).…”
mentioning
confidence: 99%